2004
DOI: 10.1111/j.1365-2370.2004.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

The intercellular adhesion molecule‐1 (ICAM‐1) gene K469E polymorphism is not associated with ischaemic heart disease: an investigation using family‐based tests of association

Abstract: The possible role of the K469E polymorphism in the intercellular adhesion molecule-1 (ICAM-1) gene in the susceptibility to ischaemic heart disease (IHD) was investigated in a well-defined Irish population using two recently described family-based tests of association. One thousand and twelve individuals from 386 families with at least one member prematurely affected with IHD were genotyped for the ICAM-1 K469E polymorphism. Using the combined transmission disequilibrium test (TDT)/sib-TDT and the pedigree dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
(48 reference statements)
0
12
0
1
Order By: Relevance
“…Previously, it was demonstrated that GG genotype of rs5498 may be related to a greater risk of the peripheral artery occlusive disease [10]. Some authors did not observe an association between rs5498 and myocardial infarction or ischemic heart disease [23][24][25]. The role of rs5498 polymorphism has been investigated in other inflammatory or immunological diseases in different populations [17,22,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was demonstrated that GG genotype of rs5498 may be related to a greater risk of the peripheral artery occlusive disease [10]. Some authors did not observe an association between rs5498 and myocardial infarction or ischemic heart disease [23][24][25]. The role of rs5498 polymorphism has been investigated in other inflammatory or immunological diseases in different populations [17,22,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, McGlinchey et al [26] found no association between the K469E polymorphism in the ICAM-1 gene and CHD in a well-defined Irish population. Also in a study of 303 Iranian patients with angiographically documented CAD, no association was found between K469E polymorphism and CHD and MI [27].…”
Section: Discussionmentioning
confidence: 96%
“…Mc Glinchey et al [34] found no association between the ICAM-1 K469E polymorphism and CHD in a well-defined Irish population; Aminian et al [35] failed to find any significant differences between CHD patients and controls regarding KK genotype, despite of their high frequencies in CHD patients in a population from Fars province, Iran; and a Slovenian study reported that the K469E polymorphism of the ICAM-1 gene was not associated with MI in subjects with diabetes mellitus [36]. …”
Section: Discussionmentioning
confidence: 99%